DEVELOPING VIRTUAL LEARNING MODELS TO ENHANCE CRITICAL THINKING AND MATERNAL NURSING PRACTICE COMPETENCY - Dini Rudini; Muthia Mutmainah (Khazanah Multidisiplin, 2024)
The COVID-19 pandemic has significantly impacted nursing education, necessitating the development of virtual learning models and media to improve critical thinking and maternal nursing competencies. This study aimed to develop an interactive virtual learning model based on problem-based learning and to assess its effectiveness in enhancing nursing students' critical thinking skills in maternal nursing practice. The development model (Define, Design, Develop, and Disseminate) was applied to create a virtual learning model. Data was collected using questionnaires to assess the validity and practicality of the developed model. The results demonstrated that the virtual learning model developed using the problem-based learning approach was valid for application in the learning process. After testing, the virtual learning model was found to be practical and effective in optimizing the implementation of learning and in improving student learning outcomes. The study concluded that the developed virtual learning model is a valid and practical tool for enhancing critical thinking skills and maternal nursing practice competencies. These findings contribute to addressing the knowledge gap in the literature regarding the effectiveness of virtual learning models in improving maternal nursing practice competencies, particularly in the context of critical thinking. This study highlights the importance of integrating technology and innovative learning approaches to adapt to the challenges posed by the COVID-19 pandemic and prepare nursing students for the demands of the 21st century.